PYROLYSIS OF CASSAVA BAGASSE INTO BIO-OIL USING Ni/NZA CATALYSTS - Jefriadi Jefriadi; Syaiful Bahri; Sunarno Sunarno; Rinny Jelita (Konversi, 2019)
Cassava bagasse is a solid tapioca industry waste that can be used as an energy source. In this study, cassava bagasse was pyrolyzed to produce bio-oil and studied the effect of Ni/NZA catalysts on yield, heating value and distribution of bio-oil products. The making of Ni/NZA catalyst starts with the process of activating natural zeolite to produce natural zeolite activated (NZA). Furthermore, impregnation of Ni metals in NZA with Ni levels 1, 2 and 3% w/w (Ni/NZA). The next step is calcination, oxidation and reduction. Cassava is peeled, shredded, washed, filtered and dried and then mashed and screened with a 60 and 80 mesh sieve to obtain cassava bagasse biomass with a size of -60+80 mesh. 50 grams of cassava bagasse with 500 ml silinap and 1.5 gram Ni/NZA catalyst are pyrolyzed at 320oC with nitrogen gas flow of 80 mL/min. Bio-oil products are analyzed by the heating value and distribution of the products. The yield of bio-oil obtained on pyrolysis using 0% Ni/NZA was 54.27% and pyrolysis using 2% Ni/NZA obtained the highest yield of 61.87%. The highest bio-oil heating value was obtained in pyrolysis using 0% Ni/NZA which is 46.78 MJ/kg and lower with increasing Ni levels in NZA. The results of GC-MS analysis of the bio-oil products showed that the use of 1% Ni/NZA catalyst significantly increased the percent area of several components i.e. 2,4,4-trimethy-l-1-Pentene, 2,5-dimethyl-2,4-Hexadiene, and 2,4,4-trimethyl-2-Pentene and decreases the percent area of some other components i.e. 1-bromo-3-methyl-Cyclohexane, 2-methyl-1-Propene,tetramer, 1-(1,1-dimethylethoxy)-3-methyl-Cyclohexene and 3-(3,3-dimethylbutyl)-Cyclohexanone.